Administrative Actions - Milkov, Dragan; Radošević, Ratko S. (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
As a part of its activities, the public administration passes and performs various acts. Among the acts of administration of non-legal, i.e. material character, given the fact that they do not have a direct legal effect, administrative actions are also included. However, there is no agreement on the notion of administrative actions in domestic legal theory. There is no even unity in the way administrative actions are regulated in domestic law. The paper therefore analyses various theoretical notions of administrative actions, and then the legal regime of administrative actions, especially bearing in mind the manner in which they are regulated in the new General Administrative Procedure Act.
Keywords: acts of administration, material acts of administration, administrative actions